2014
DOI: 10.1088/0004-637x/787/1/15
|View full text |Cite
|
Sign up to set email alerts
|

HIGH-ENERGY GAMMA-RAY EMISSION FROM SOLAR FLARES: SUMMARY OFFERMILARGE AREA TELESCOPE DETECTIONS AND ANALYSIS OF TWO M-CLASS FLARES

Abstract: We present the detections of 19 solar flares detected in high-energy gamma rays (above 100 MeV) with the Fermi Large Area Telescope (LAT) during its first four years of operation. Interestingly, all flares are associated with fairly fast Coronal Mass Ejections (CMEs) and are not all powerful X-ray flares. We then describe the detailed temporal, spatial and spectral characteristics of the first two long-lasting events: the 2011 March 7 flare, a moderate (M3.7) impulsive flare followed by slowly varying gamma-ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(114 citation statements)
references
References 22 publications
5
108
1
Order By: Relevance
“…Time-extended nuclear gamma-ray emission, sometimes persisting over more than ten hours, was discovered by the GAMMA 1 mission (Akimov et al 1996) and the Compton Gamma-Ray Observatory (Kanbach et al 1993). The recent FERMI observations with much higher sensitivity have shown that this emission occurs rather often, even in moderate flares (Ackermann et al 2014). The greater altitude of the acceleration region and the possibly reduced access of the particles to the dense low solar atmosphere -depending on the magnetic field configurationcould explain why no such gamma-ray signatures were detected with other GLEs in the past.…”
Section: Discussionmentioning
confidence: 99%
“…Time-extended nuclear gamma-ray emission, sometimes persisting over more than ten hours, was discovered by the GAMMA 1 mission (Akimov et al 1996) and the Compton Gamma-Ray Observatory (Kanbach et al 1993). The recent FERMI observations with much higher sensitivity have shown that this emission occurs rather often, even in moderate flares (Ackermann et al 2014). The greater altitude of the acceleration region and the possibly reduced access of the particles to the dense low solar atmosphere -depending on the magnetic field configurationcould explain why no such gamma-ray signatures were detected with other GLEs in the past.…”
Section: Discussionmentioning
confidence: 99%
“…The same conclusion can be reached about other events reported by Ackermann et al (2012b) to have impulsive >100 MeV phases. Specifically, Share et al (2017) find that the first >100 MeV outburst on 2012 Mar 7 described in detail by Ackermann et al (2014) was distinct sustained emission and not directly associated with the X5.4 flare. LAT event (data points and˙1 statistical uncertainties).…”
Section: Long-duration -Ray Eventsmentioning
confidence: 96%
“…The emission was delayed about 10 s from the associated hard X-ray and nuclear-line emission and there was no evidence for any >100 MeV -ray emission in the hours after the flare. The Fermi/LAT team reported the detection of 18 >100 MeV events associated with solar flares covering the time period from 2008 August to 2012 August (Ackermann et al 2014) which they classified as being impulsive, sustained, or delayed. In some cases they categorized the events as having both impulsive and sustained characteristics.…”
Section: New Insights Of Sustained Emission Events From Fermi Observamentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the 2011 Mar 7 and 2011 Jun 7 -ray observations and related solar measurements were also presented in Ackermann et al (2014). The March 7 event was reported as having both impulsive and sustained emission components, while the June 7 event was classified as only having sustained emission because -rays were detected in only one LAT exposure about 1 h after the flare and there was no exposure to the flare.…”
Section: New Insights Of Sustained Emission Events From Fermi Observamentioning
confidence: 99%